Motivation for sports practice and its relationship with the level of physical activity and satisfaction with practice in children - Fin,Gracielle (2025)
ABSTRACT This study analysed the relationship between motivation to practice sports, satisfaction with practice, and the level of physical activity in children aged 7 to 11. A total of 1,089 students from public schools in the Midwest of Santa Catarina, Brazil, took part. Motivation was assessed using the Pictorial Scale of Children’s Sports Motivation, satisfaction was measured using a visual analog scale of happiness, and the level of physical activity was evaluated using the Previous Day’s Physical Activity Questionnaire. Exploratory and confirmatory factor analyses confirmed the validity and reliability of the Pictorial Scale of Children’s Sports Motivation. Structural equation modeling was used to test the proposed hypothetical model. The results showed that intrinsic motivation was the main predictor of satisfaction with the practice, followed by extrinsic motivation, while demotivation had a significant negative effect. Satisfaction, however, did not directly predict the level of physical activity. Boys were significantly more active than girls, although both showed high levels of intrinsic motivation for sport. The findings highlight the importance of promoting intrinsic motivation in childhood to increase satisfaction with sport. Additional strategies may be needed to transform motivation into greater physical involvement.